Comparing same day sputum microscopy with conventional sputum microscopy for the diagnosis of tuberculosis--Chhattisgarh, India. - Priyakanta Nayak (Public Library of Science (PLoS), 2013)
Background The World Health Organization (WHO) recommends same day sputum microscopy (spot-spot) in preference to conventional strategy (spot-morning) for the diagnosis of smear positive tuberculosis with the view that completing diagnosis on a single day may be more convenient to the patients and reduce pre-treatment losses to follow-up. Methods We conducted a cross-sectional study in seven selected district level hospitals of Chhattisgarh State, India. During October 2012 - March 2013, two sputum specimens (spot-early morning) were collected from consecutively enrolled adult (≥ 18 years) presumptive TB patients as per current national guidelines. In addition, a second sample was collected (one hour after the collection of first spot sample) from the same patients. All the samples were examined by ziehl-Neelsen (ZN) microscopy. McNemar's test was used to compare statistical differences in the proportion smear positive between the two approaches (spot-spot versus spot-morning). Results Of 2551 presumptive TB patients, 69% were male. All patients provided the first spot specimen, 2361 (93%) provided the second spot specimen, and 2435 (96%) provided an early morning specimen. 72% of specimens were mucopurulent in conventional strategy as compared to 60% in same day strategy. The proportion of smear-positive patients diagnosed by same day microscopy was 14%, as compared to 17% by the conventional method (p<0.001). A total of 73 (16.9%) potential cases were missed by the same day method compared to only 2 (0.5%) by the conventional method. Conclusion Same-day microscopy method missed 17% of smear-positive cases and contrary to prior perception, did not increase the proportion of suspects providing the second sample. These findings call for an urgent need to revisit the WHO recommendation of switching to same-day diagnosis over the current policy.